(untitled) (LEARNing Landscapes, 2018)
This article presents the reflections of The Self-Study Group, a community of teacher educators and scholars. In this article, we utilize the theoretical framework of Bildung and the literary genre of Bildungsroman to explore the work of being a teacher educator. Drawing upon the results of a narrative self-study, we explore how, for individual teacher educators, the significance of teacher education stems from one’s life story, including lived experiences from being a child, being a student, and being a teacher. We argue that the acts of authoring and telling of stories have the potential to illuminate the interconnected nature of the personal and the professional dimensions of teacher educator self-formation.